2011
DOI: 10.1590/s1808-86942011000100015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos níveis séricos de testosterona em pacientes com síndrome da apneia obstrutiva do sono

Abstract: Mal es with obstructive sleep apnea syndrome (OSAS) may present decreased testosterone serum levels because of hypoxemia. Aim:To correlate testosterone levels in OSAS patients with laboratory parameters. Material and methods:103 registries of OSAS patients were reviewed from 2002 to 2009. The following data collected: age when polysomnography was done, hematocrit and hemoglobin levels, total testosterone serum levels, BMI, apnea/hypopnea index (AHI), and O2 saturation.Study Design: A cross-sectional retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Additionally, dilatation of the upper airway depends on contraction of certain dilator muscles (e.g. the genioglossus), which is mediated by serotoninergic and noradrenergic neurons travelling in parallel . Both may be affected by age and androgen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dilatation of the upper airway depends on contraction of certain dilator muscles (e.g. the genioglossus), which is mediated by serotoninergic and noradrenergic neurons travelling in parallel . Both may be affected by age and androgen levels.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be some effect of sleep fragmentation and hypoxia 22. Other data also suggests that BMI may be the primary determinant of testosterone in men with OSA,23 including a cross-sectional retrospective case study of 103 registries of OSAS patients from 2002 to 2009 24. In cohort of 1312 men aged 65 years and older at baseline and followed for 3.4 years it was shown that total testosterone levels were unrelated to age or duration of sleep, but was inversely related to the AHI and ODI.…”
Section: The Effect Of Specific Sleep Abnormalities On Testosteronementioning
confidence: 99%
“…The rise of testosterone is mostly dependent on sleep integrity, generally reaching its peak during the first 3 h of uninterrupted sleep (10); indeed, a reduced LH pulsatility and serum total testosterone has been found to be associated with sleep fragmentation and/or intermittent hypoxia occurring in patients with OSA syndrome (12, 13). However, it has been suggested that serum testosterone levels may be affected primarily by obesity in men with OSA syndrome (14, 15). Indeed, the association of testosterone levels with sleep quality and sleep-disordered breathing was absent or markedly attenuated after adjusting for body mass index (BMI) or waist circumference (16).…”
Section: Introductionmentioning
confidence: 99%